Análise de custos em uma linha de produção de uma padaria na cidade de Mossoró/RN - Fonseca, Raquel de Araújo (Universidade Federal Rural do Semi-Árido, 2019)
In any commercial or manufacturing segment, the consumer market determines what is consumed, it would be no different in the bakery industries. Once considered items of necessity, baked products need to be tailored to consumer needs, combining good product acceptance and fair price, ensuring that the product sold pays its costs and generates profit. The help of costing methods and production cost analysis allows the manager to know how much he spends to produce and sell a unit of his product. This current study analyzes the production costs of bread making in a small bakery in the city of Mossoró / RN, with the objective of identifying the mark-up, based on the selling price worked by the company, comparing the even with the projection of what is considered ideal by the owner.
Monografia
Keywords: Métodos de custeio; Pão francês; Custos; Panificadora; Mark-up; ENGENHARIAS::ENGENHARIA DE PRODUCAO